Does Islamic Finance Matter for Poverty Development in Indonesia? - Rachmania Nurul Fitri Amijaya; Andika Eko Prassetyo; Rensia Yuliati Pratama; Intan Wardah Kharisma (Airlangga Journal of Innovation Management, 2023)
Poverty remains a multifaceted economic challenge that necessitates a variety of solutions. The method that must be pursued focuses on enhancing economic, social wellbeing, and equalizing people's purchasing power to satisfy life's requirements rather than only economic growth. The purpose of this study is to discover and assess the impact of mudharabah finance, zakat, and inflation on poverty alleviation in Indonesia, both individually and collectively. The data utilized is secondary data from associated agencies such as the Financial Services Authority (OJK), the National Zakat Amil Agency (BAZNAS), Bank Indonesia (BI), and the Central Agency of Statistics (BPS) for 2006-2022 period. The study employed a multiple linear regression model and hypothesis testing utilizing E-Views 12 Software, with mudharabah funding, zakat, and inflation serving as independent factors and poverty level serving as the dependent variable. The findings of the regression tests show that mudharabah and zakat finance have a considerable negative influence on poverty, but the inflation rate has a negligible positive effect on poverty. The government, as a policymaker, can maximize the distribution of mudharabah and zakat finance for poverty alleviation initiatives; nevertheless, government must continue to pay attention to the inflation rate in order to regulate and distribute people's buying power in a balanced manner.